TINGKAT PELAYANAN RUAS JALAN TEUKU UMAR DAN JALAN SETIABUDI KOTA SEMARANG DI TINJAU DARI ASPEK PERMASALAHAN KEMACETAN LALU LINTAS - Agung Hendra Kusumo; Tjoek Suroso Hadi (Jurnal Planologi, 2017)
Traffic congestion is a classic problem in big cities especially in developing countries such as Indonesia. Many things can be the cause of the traffic jam, for it is necessary to research on traffic congestion as much as possible, with the hope of producing the best solution for all.Congestion that occurs due to the activity and mixing between local and regional flows. The purpose of this study is to analyze the level of service and performance road cut Teuku Umar street and road Setiabudi, so it can be arranged alternative actions that can be done to address the problem of traffic congestion.The method used in this research is by using Quantitative Deductive Method Rationalistic, with retrofitting Level of Service and analysis of motion control (maneuver) in order to see the level of service road and the movement of traffic in motion over Jatingaleh Region Semarang. The results of this study is the identification of the causes of traffic congestion and the suitability of the performance in the study area (Region Jatingaleh).Level of service for road Jatingaleh area is the level of F means that hampered the flow of traffic, low speed, volume over capacity, congestion often occurs at a time long enough so that it can drop to zero. In the piece Jalan Teuku Umar and Jalan Setiabudi there are several types of motion control, there are approximately 5 crossing, diverging 6, 7 merging and 3 weaving. Seeing the condition of the poor level of service in most of the observation point, of course, reduce the performance of the maneuver crossing the road.Need for the recommendation that a new path with the added solution of the motion control analysis (maneuver) in the form of Grade Separation, can be Overpass (Flyover) or underpass.Keywords: transportation, congestion, road, and traffic.